RUNX1 and TGF‐β signaling cross talk regulates Ca2+ ion channels expression and activity during megakaryocyte development. (1st May 2020) - Raghuwanshi, Sanjeev; Dahariya, Swati; Sharma, Durga Shankar; Kovuru, Narasaiah; Sahu, Itishri; Gutti, Ravi Kumar
Abstract : Thrombocytopenia is characterized by low platelet count and is typically observed among all preterm and low birthweight neonates admitted to the neonatal intensive care unit. Although the underlying cause for this predisposition is unclear, recent studies have proposed that the intrinsic inability of neonatal hematopoietic stem/progenitor cells to produce mature polyploid megakaryocytes (MKs) may result in delayed platelet engraftment. The developmental and molecular differences between neonatal and adult MKs are not yet fully understood. Previously, we had reported that the key MK transcription factor RUNX1, which is crucial for the regulation of MK specification and maturation, is down‐regulated in neonatal MKs when compared with adult MKs. In humans, loss‐of‐function mutations in RUNX1 cause familial platelet disorder, which is characterized by thrombocytopenia, indicating its crucial role in MK development. However, information about its cross talk with developmentally regulated signaling pathways in MKs is lacking. In this study, we performed a differential gene expression analysis in MKs derived from human cord blood (CB) and adult peripheral blood (PB) CD34 + cells. Further, validation and correlation studies between RUNX1 and transforming growth factor beta (TGF‐β) were performed in a differentiating megakaryocytic cell line model. The analysis revealed that TGF‐β pathway was the main pathway affected between CB‐ and PB‐MKs. RUNX1 is reported to be a modulator of TGF‐β signaling in several studies. The correlation between RUNX1 and TGF‐β pathway was analyzed in the PMA‐induced megakaryocytic differentiating K562 cells, which exhibit mature megakaryocytic features. The RT 2 profiler PCR array analysis revealed that TGF‐β pathway components were up‐regulated in the PMA‐induced megakaryocytic differentiating cells. Furthermore, our study indicated that human TGF‐β1 promotes cytosolic calcium (Ca 2+ ) activity and MK maturation. We noticed that TGF‐β1 increased intracellular free Ca 2+ ([Ca 2+ ]i) via reactive oxygen species‐mediated activation of transient receptor potential (TRP) ion channels. Moreover, we observed that decreased cytosolic Ca 2+ activity in the siRUNX1‐transfected cells was associated with down‐regulation of TRP ion channel expression. Finally, we demonstrated that TGF‐β/SMAD signaling augments the development of MKs derived from CB‐CD34 + . Present data suggest that RUNX1/TGF‐β pathway cross talk is crucial for MK maturation. Abstract : Megakaryocytes (MKs) release latent TGF‐β with secretory granules, which is activated following extracellular matrix remodeling. Autocrine TGF‐β binding to TGF‐βRs initiates intracellular signaling events and eventually regulates target gene expression and reactive oxygen species (ROS) production, which functionally interacts with channel proteins and increases Ca 2+ entry. The transcription factor RUNX1 augments the effects of TGF‐β and Ca 2+ entry by transcriptional regulation of transient receptor potential ion channels. Thus, RUNX1/TGF‐βR signaling cross talk accelerates terminal MK maturation.